Transcriptome analysis explores genes related to shikonin biosynthesis in Lithospermeae plants and provides insights into Boraginales’ evolutionary history - Wu, Feng-Yao (Sci Rep, 2017)
Shikonin and its derivatives extracted from Lithospermeae plants’ red roots have current applications in food and pharmaceutical industries. Previous studies have cloned some genes related to shikonin biosynthesis. However, most genes related to shikonin biosynthesis remain unclear, because the lack of the genome/transcriptome of the Lithospermeae plants. Therefore, in order to provide a new understanding of shikonin biosynthesis, we obtained transcriptome data and unigenes expression profiles in three shikonin-producing Lithospermeae plants, i.e., Lithospermum erythrorhizon, Arnebia euchroma and Echium plantagineum. As a result, two unigenes (i.e., G10H and 12OPR) that are involved in “shikonin downstream biosynthesis” and “methyl jasmonate biosynthesis” were deemed to relate to shikonin biosynthesis in this study. Furthermore, we conducted a Lamiids phylogenetic model and identified orthologous unigenes under positive selection in above three Lithospermeae plants. The results indicated Boraginales was more relative to Solanales/Gentianales than to Lamiales.